Physiological Insights into Elite Sprint Paddlers: Unravelling Performance Dynamics and Training Implications - Suchishrava Dubey; Prashant Kumar Choudhary (OVS LLC, 2023)
Study purpose. This study aimed to investigate the relationship between physiological reactivity and sprint paddling performance among elite athletes, focusing on cardiorespiratory responses, metabolic efficiency, and energy utilization patterns. Materials and methods. A group of N= 20 elite sprint paddlers from various regions in India was meticulously selected for this study. Detailed assessments of cardiorespiratory responses, metabolic efficiency, and energy utilization patterns were conducted using standardized protocols and cutting-edge measurement techniques. Individual differences among athletes were carefully documented. Results. The study revealed a remarkable homogeneity among the athletes, reflecting stringent training standards. However, intriguing individual differences emerged, particularly in cardiorespiratory reactivity. Athletes with swift neural responses and adept metabolic acidosis adaptation showcased enhanced overall performance, indicating the critical role of the nervous system and efficient respiratory mechanisms in optimizing paddlers' capabilities. Analysis of CO2 emissions and lactate concentrations indicated a balanced energy utilization pattern and optimal anaerobic metabolism and respiratory responses. Balancing anaerobic alactate and lactate capacities emerged as pivotal. Conclusions. The findings underscore the need for targeted training programs that leverage individual differences, enhance neural adaptations, and metabolic acidosis tolerance, and optimize energy pathways. These transformative insights offer coaches, sports scientists, and athletes valuable tools to elevate performance outcomes. The study enriches our understanding of sprint paddling and serves as a paradigm for studying elite athletic performance, guiding the future of sports science and coaching. Future research avenues include exploring the long-term impact of tailored training interventions, investigating molecular mechanisms of cardiorespiratory reactivity, and studying psychological aspects of athletic performance. Comparative studies across diverse sports disciplines promise universal insights into elite athletic performance.